Linux command line and shell scripting bible - Blum, Richard, 1962-; Bresnahan, Christine (John Wiley & Sons, 2015)
Talk directly to your system for a faster workflow with automation capability Linux Command Line and Shell Scripting Bible is your essential Linux guide. With detailed instruction and abundant examples, this book teaches you how to bypass the graphical interface and communicate directly with your computer, saving time and expanding capability. This third edition incorporates thirty pages of new functional examples that are fully updated to align with the latest Linux features. Beginning with command line fundamentals, the book moves into shell scripting and shows you the practical application.- Resumé vydavatel
Includes index.
Keywords: Linux.; Linux (operační systém); operační systémy; skriptové jazyky; Linux (operating system); operating systems; script languages; elektronické knihy; příručky; electronic books; handbooks and manuals